Catena-Poly[Tris(?3-Acetylacetonato)Nickelate(Ii)Sodium(I)] - Venegas-Yazigi, D; Venegas-Yazigi, D (2013)
The title complex, [NaNi(C5H7O2) 3]n, contains an anionic tris(acetylacetonato) nickelate(II) unit, [Ni(acac)3]- (acac is acetylacetonate), with a highly regular octahedral coordination geometry. The NiII cation lies on a Wyckoff a site, resulting in D3 symmetry of the anion. Charge balance is provided by sodium cations, which occupy Wyckoff type b sites. Each sodium cation is surrounded by two [Ni(acac)3]- anions, each of which is connected to the alkali metal through three O atoms, in a fac configuration. This arrangement leads to the formation of linear [Na{Ni(acac)3}] n chains along the c axis. The Ni···Na distance is 2.9211 (10) Å. The title complex is one of the few examples of heterometallic systems based on alkali and transition metal cations bridged by acetylacetonate ligands. © 2013 International Union of Crystallography.